اغتصاب الزوجة في القانون محو العنف العائلي الإندونيسي مقارنا بالفقه الإسلامي - Ismanto, Reno (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
The purpose of this research is to analyze the issue of marital rape provided in the law on the elimination of family violence - Law No. 23 of 2004th- and the draft of book of Indonesian criminal law, compared to Islamic jurisprudence through the views of scholars in the case. The research found the following results: there is difference in meaning of term of rape between Islamic jurisprudence and Indonesian Law. The term of rape in Islamic Jurisprudence formed from two elements: forbidden intercourse and coercion. While the rape in Indonesian Law is based on the absence of choice in intercourse, and its applicable to married and unmarried persons. Although the Islamic Juriprudence and Indonesian Law have same views in prohibition any actions of violence againts women, however the difference between two laws in the concept of the rape has implications in type of punishmen toward this crime.